101 Interesting Cases in Clinical Medicine - Azad, K. A. K. Khan Abul Kalam; Kabir, A. Ahmedul; Amin, M. R. Mohammad Robed (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the 101 interesting cases in clinical medicine. Internal medicine is a subject of inquisitiveness and search for the hidden. Sometimes common diseases present in an uncommon way while atypical diseases present in the common way, which requires sound understanding of the whole scenario and critical analysis to finally discover the cases as interesting or rare disease. This book unfolds 101 interesting cases in an amazing way with a sequential exploration of newer dimensions of thinking as one would go through the pages ahead. This book seems to be very exciting and challenging to readers as they will go through case-by-case exploring the answers of all questions in mind in a fascinating way. This book will reach to the widest possible readers, including medical students, postgraduate trainees, and physicians of all stages.